Descriptive Cross-Sectional Study on Knowledge, Awareness, and Adherence to Medication among Hypertensive Patients at a Tertiary Care Centre in Colombo District, Sri Lanka - S. Pirasath; A. G. H. Sugathapala; K. Wanigasuriya (International Journal of Hypertension)
Objective. This study was aimed to assess the patient’s knowledge and awareness about hypertension and adherence to antihypertensive medication among hypertensive patients. Methods. The descriptive cross-sectional study was conducted in three medical clinics of Colombo South Teaching hospital, Kalubowila, Sri Lanka, from April 2019 to September 2019. Total of 384 hypertensive patients were recruited by systematic randomized controlled sampling and interviewed with validated questionnaires to assess their knowledge about hypertension and adherence to antihypertensive medication. Data were analyzed using SPSS (version 21) analytical package, and the chi-squared test was performed. Results. The total sample consisted of 384 hypertensive patients with a mean age of 59.32 (±12.34SD). This included 180 (46.9%) males and 204 (53.1%) females. The male : female ratio was approximately 9 : 10. Most of patients were with primary and ordinary educational status (65.9%), normal body mass index (54.9%), mild elevation of LDL cholesterol (76.3%), and coexistent ischemic heart disease (39.6%). The knowledge about hypertension among majority of patients was reasonable. However, they were unaware about normal values of blood pressure (69%, 95% of CI 1.92–2.09) and diagnostic values of hypertension (90.1%, 95% of CI 2.26–2.40). Moreover, they were unaware of their blood pressure values at time of diagnosis (75.3%, 95% of CI 2.09–2.25), at recent clinic visit (71.3%, 95% of CI 2.0-2.17), and target level (81.8%, 95% of CI 2.25-2.41). Most patients had adequate knowledge about the risk factors and complications of hypertension and were aware of their target organ damage (70.3%). Most patients believed that medication alone is not sufficient to control blood pressure (41.7%, 95% of CI 1.40-1.51) and adequate control of their blood pressure reduces complications (68.2%, 95% of CI 1.37-1.51). Most of the patients (71.8%) had reasonable good drug compliance. The forgetfulness was commonly attributed for nonadherence (69%, 95% of CI 1.26-1.36). Conclusions. The knowledge about hypertension among majority of patients was reasonable. But, they were unaware about their disease status and their diagnosis, target, and recent blood pressure values. Most of patients had adequate knowledge about the risk factors and complications of hypertension. However, they were unaware about their target organ damage due to hypertension. The drug compliance was reasonable among them. The forgetfulness was common reason for nonadherence. Therefore, healthcare professionals should implement individualized educational programmes to increase the awareness of disease status, appropriate blood pressure levels, and adherence of treatment to improve the outcome of patients.